KEWENANGAN DESA ADAT DALAM PENGELOLAAN KEPARIWISATAAN BUDAYA BALI DALAM PERSPEKTIF PERATURAN DAERAH NOMOR 4 TAHUN 2019 TENTANG DESA ADAT - Yanti, A.A. Istri Eka Krisna (Jurnal Hukum Saraswati (JHS), 2019)
This reseach focuses to analyze the authority of the Desa Adat (traditonal village in Bali) in managing Balinese Culture Tourism, because Balinese Culture is the main attraction of Balinese tourism which is determined by the government as the main foundation in the development of Balinese tourism. Balinese culture is implemented, maintained and developed by the Balinese customary law community in Desa Adat, so that in this reseach the writer is interested in two legal problems; 1. What is the arrangement of village dualism in Bali to managing Balinese Culture Tourism? 2. What is the authority of Desa Adat in managing Balinese Culture tourism based on Regional Regulation Number 4 of 2019 regarding Desa Adat?. The research method used in this study is a normative research method with a focus on legislation and literature that is relevant to the research topic. Based on research study, there are several forms of villages in Bali are overlapping (Desa Adat and Desa Dinas).However, based on Regional Regulation Number 4 of 2019 regarding Desa Adat, the Desa Adat is authorized to manage tourist destinations which are the original right of the Adat Village moreover.